Crossed Fused Renal Ectopia: Presentations on 99mTc-MAG3 Scan, 99mTc-DMSA SPECT, and Multidetector CT. (October 2015) - Moon, Eun Ha; Kim, Min-Woo; Kim, Young Jun; Sun, In O
Abstract : Abstract: Crossed renal ectopia is an uncommon developmental anomaly in which both kidneys are located on the same side of the body. The present case describes a 20-year-old man who underwent the military entrance physical examination. The ultrasound showed the right kidney in normal site with slightly increased size, but the left kidney was not identified. 99m Tc-MAG3 scan showed a single kidney with 2 ureters, and the orifices of the ureters were connected at both sides of bladder. 99m Tc-DMSA SPECT and contrast-enhanced multidetector CT were performed and revealed crossed fused renal ectopia.